Major Oncogenic Drivers and Their Clinicopathological Correlations in Sporadic Childhood Papillary Thyroid Carcinoma in Belarus - Rogounovitch, Tatiana I. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Childhood papillary thyroid carcinomas (PTCs) detected after the Chernobyl accident were genetically characterized by a high prevalence of gene rearrangements and low frequency of point mutations. However, no reports on genetic alterations in sporadic childhood PTCs from the Chernobyl-affected regions are available. This study investigated a series of PTCs from children of Belarus not exposed to radiation, and found that fusion genes were significantly more prevalent than point mutations in these tumors. Clinicopathologically, RET/PTC3 was associated with solid growth pattern and higher tumor aggressiveness, BRAF(V600E) and RET/PTC1 with classic papillary morphology and mild clinical phenotype, and ETV6ex4/NTRK3 with follicular-patterned PTC and the reduced aggressiveness. The spectrum of driver mutations in sporadic childhood PTC largely parallels that in Chernobyl PTC, although the distribution of oncogene types suggests less aggressive clinical presentation of sporadic PTC, especially than that of early-onset radiation-related PTC. ABSTRACT: Childhood papillary thyroid carcinoma (PTC) diagnosed after the Chernobyl accident in Belarus displayed a high frequency of gene rearrangements and low frequency of point mutations. Since 2001, only sporadic thyroid cancer occurs in children aged up to 14 years but its molecular characteristics have not been reported. Here, we determine the major oncogenic events in PTC from non-exposed Belarusian children and assess their clinicopathological correlations. Among the 34 tumors, 23 (67.6%) harbored one of the mutually exclusive oncogenes: 5 (14.7%) BRAF(V600E), 4 (11.8%) RET/PTC1, 6 (17.6%) RET/PTC3, 2 (5.9%) rare fusion genes, and 6 (17.6%) ETV6ex4/NTRK3. No mutations in codons 12, 13, and 61 of K-, N- and H-RAS, BRAF(K601E), or ETV6ex5/NTRK3 or AKAP9/BRAF were detected. Fusion genes were significantly more frequent than BRAF(V600E) (p = 0.002). Clinicopathologically, RET/PTC3 was associated with solid growth pattern and higher tumor aggressiveness, BRAF(V600E) and RET/PTC1 with classic papillary morphology and mild clinical phenotype, and ETV6ex4/NTRK3 with follicular-patterned PTC and reduced aggressiveness. The spectrum of driver mutations in sporadic childhood PTC in Belarus largely parallels that in Chernobyl PTC, yet the frequencies of some oncogenes may likely differ from those in the early-onset Chernobyl PTC; clinicopathological features correlate with the oncogene type.